Usefulness of diaphragmatic ultrasound in a patient with Guillain Barré syndrome: Case report - Cachay Diaz, Jordy Deyby (2025)
Introduction: Guillain-Barré syndrome (GBS) is an acute inflammatory neuropathy that can cause respiratory paralysis and require mechanical ventilation. Diaphragmatic ultrasound is useful for assessing respiratory function in these patients and guiding ventilator weaning. Case report: We present the case of a 16-year-old adolescent with GBS and progressive respiratory failure, admitted to the Intensive Care Unit on mechanical ventilation and vasoactive support. Chest CT revealed left atelectasis, confirmed by fiberoptic bronchoscopy. Subsequently, diaphragmatic ultrasound showed excursion less than 10 mm, indicating muscle dysfunction. A tracheostomy and respiratory rehabilitation were initiated, with progressive clinical and functional improvement. Conclusion: Diaphragmatic ultrasound allowed for early identification of diaphragmatic dysfunction, facilitating key therapeutic decisions such as tracheostomy. Its use in critically ill patients with Guillain-Barré syndrome represents a valuable, noninvasive, and safe tool for optimizing ventilatory management and improving clinical outcomes. Keywords: Guillain-Barré syndrome; Diaphragm ultrasound; Diaphragm dysfunction; Mechanical ventilation; Intensive Care Unit (Source: MeSH-NLM).